Properties of modified bitumen in hot mix asphalt using crumb rubber - Hashimah, Mohd Hadzri (2017)
Today capacity or volume of the road user increases year by year is one of the factors that make the road pavement prone to defect or damage such as cracking. Therefore, the use of Crumb Rubber Modifiers (CRM) in flexible pavements to improve characteristics of bitumen binders has become a technique of great potential in recent year. This thesis presents a study to develop mix design for Hot Mix Asphalt (HMA) using additive of crumb rubber. The gradations used are AC 14 based on Public Works Department of Malaysia’s (PWD Malaysia) Standard Specification of Road Works (JKR/SPJ/2008). CRM with varying percentages of 1%, 2% and 3% percent by total weight of bitumen were studied. The range percentage of bitumen binder was used in this study is 4% until 6%. All the mix samples were based on the Marshall Mix Design Method. In this study, the volumetric properties such as Marshall Stability, flow, air voids (AV), voids filled with bitumen (VFB), bulk density and stiffness were investigated. The 2% of crumb rubber added in bitumen binder has been selected to be the optimum percentage of crumb rubber in HMA mix because all the volumetric properties complied with the requirements of PWD Malaysia’s Standard Specification of Roads. Based on the result obtained, there were significant effect in volumetric properties between unmodified and modified bitumen. Besides that, penetration and softening point were also performed on modified bitumen. The results show that addition of CRM to bitumen binder has significant influence on its properties. From the laboratory results showed an increase in softening point and stiffness of the binder. It could concluded that CRM shows positive effect to the bitumen binder.